Numerical prediction of noise generated from airfoil in stall using LES and acoustic analogy. (November 2021) - Aihara, Aya; Goude, Anders; Bernhoff, Hans
This article presents the aerodynamic noise prediction of a NACA 0012 airfoil in stall region using Large Eddy Simulation and the acoustic analogy. While most numerical studies focus on noise for an airfoil at a low angle of attack, prediction of stalled noise has been made less sufficiently. In this study, the noise of a stalled airfoil is calculated using the spanwise correction where the total noise is estimated from the sound source of the simulated span section based on the coherence of turbulent flow structure. It is studied for the airfoil at the chord-based Reynolds number of 4.8 × 10 5 and the Mach number of 0.2 with the angle of attack of 15.6° where the airfoil is expected to be under stall condition. An incompressible flow is resolved to simulate the sound source region, and Curle's acoustic analogy is used to solve the sound propagation. The predicted spectrum of the sound pressure level observed at 1.2 m from the trailing edge of the airfoil is validated by comparing measurement data, and the results show that the simulation is able to capture the dominant frequency of the tonal peak. However, while the measured spectrum is more broadband, the predicted spectrum has the tonal character around the primary frequency. This difference can be considered to arise due to insufficient mesh resolution.